Performance of local populations of Medicago truncatula, M. laciniata and M. minima collected in the Algerian steppe areas - Chebouti A.; Meziani N.; Bessedik F.; Mefti M.; Laib M.; Amrani S. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
As part of the development of local species to be used in pastures and in crop-livestock systems in Algeria, twelve populations of Medicago truncatula, M. laciniata and M. minima were evaluated for their forage and grain yield during 2016/2017 cropping season. The study focused on dry matter yield and pod and seed production. A randomized block design with three replications was used. The results obtained show that the populations of the three species tested differ significantly for all measured variables. The study identified populations with high dry matter and seed yields. The Principal Component Analysis clearly discriminated the populations of M. minima, M. laciniata and M. truncatula. We noted that early populations of M. truncatula had the highest of pods and seeds yield.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)